Study to assess knowledge attitude and practices of antenatal care among antenatal women attending outdoor clinic in tertiary care hospital - Ahirwar, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal mortality rate in India continues to be a national challenge despite of the various measures taken by the Indian government, Non profit organizations in and outside the country including the World Health Organization. To find out the gaps between the providers and beneficiaries we tried to find out what actually prevents our pregnant women to seek Regular Antenatal Care by evaluating their knowledge, attitudes and practices towards antenatal care. Methods: All antenatal women attending outpatient clinic of department of obstetrics and gynae Gandhi medical college Bhopal over a period of one year were included in the study. Study group was of unbooked antenatal women and control group consisted of booked women at the hospital. All subjects were given a predesigned, pretested questionnaire to fill in their local language and the data thus obtained was analysed statistically. Results: 86.16% subjects visited ANC clinic during first trimester, 66.33% knew correctly about frequency of antenatal visits, 97.50% knew about Tetanus immunization. Likewise, 78.33% had positive attitude towards antenatal checkups and early registration. Similarly, 70.4% took adequate antenatal care, 93.33% took iron folic acid tablets. Conclusions: Thus, the study shows that the knowledge, attitude and practice of antenatal care is good in the booked subject the same is not the case in unbooked subjects coming to the hospital with complications or being referred to the hospital.